Diagnostic and prognostic value of glucose transporters in melanocytic lesions. Issue 6 (December 2019) - Ruby, Kristen N.; Liu, Catherine L.; Li, Zhongze; Felty, Cameron C.; Wells, Wendy A.; Yan, Shaofeng
Abstract : We have previously reported increased glucose transporter 1 (GLUT1) expression in melanoma compared to benign nevi, associated with a significantly lower survival rate. GLUT1 upregulation was highly specific for distinguishing melanoma from benign nevi, yet poorly sensitive, likely because of expression of other GLUT isoforms. The purpose of this study was to evaluate GLUT2 and GLUT3, as melanoma biomarkers. A tissue microarray, consisting of 91 primary melanomas, 18 melanoma metastases, and 56 nevi, was examined using GLUT2 and GLUT3 immunohistochemistry. A semiquantitative scoring method was used to determine the percentage of positive tumor cells and staining intensity. GLUT2 was negative in all melanomas and benign nevi examined. Increased GLUT3 expression was more frequent in melanoma than in nevi ( P < 0.0001), and in metastatic melanoma than in primary melanomas ( P < 0.001). Of melanoma cases, 85.3% expressed either GLUT1 or GLUT3 or both, 39.4% of melanoma cases coexpressed GLUT1 and GLUT3, 17.4% of melanoma cases only expressed GLUT1, 28.4% of melanoma cases only expressed GLUT3, and 14.7% of melanoma cases were negative for both markers. Patients whose melanoma exhibited a high level of GLUT3 had significantly lower survival rates than those with low GLUT3 expression ( P = 0.002). Evaluating both GLUT1 and GLUT3 increased the diagnostic value by increasing the sensitivity while the specificity remained high. In conclusion, GLUT2 was not expressed in melanocytes. GLUT3 expression was upregulated in melanoma compared with nevi, especially in those with worse prognosis. Similar to GLUT1, GLUT3 may serve as a useful diagnostic and prognostic marker.